Memorandum re Shortage of Nurses - Labour Party (Great Britain). National Executive Committee ; Labour Party (Great Britain). Advisory Committee on Public Health ; Joint Research Dept. of the Trades Union Congress and the Labour Party; MacCallum, Maude
1924-07 1924 1920s 8 pages - 3 - (92) decided in a Court of Law. We think the attitude of Hospital Authorities can be altered by placing nurses under the jurisdiction of some State Department. At present, although the Minister of Health has a certain amount of jurisdiction over the General Nursing Council for England and Wales, the G.N.C. has no jurisdiction over the hours of employment or salaries of nurses, nor has it any control over the hospitals, except with regard to education. When complaints have been made to the Minister of Health as to the dismissal and unjust treatment of probationer nurses in hospitals over which the Ministry of Health has some jurisdiction, the reply has always been that he has not power to interfere between employer and employed, except in the case of officers of high rank, whose appointment he has sanctioned. We believe that if nurses could be brought under either the Secretary of State or the Minister of Labour with regard to hours, remuneration, and signing of contracts, something in the manner the Shop Assistants and Factory Workers have been, it would be for the protection of the Profession. At present, no matter how badly a nurse may be treated, unless she has interest and money to take the matter into a Court of Law, there is no redress. We can give definite cases to prove this contention. If, therefore, a short act could be passed dealing with the hours of work, remuneration, contracts, and also include a compulsory scheme for superannuation for all Nurses in receipt of a salary, it would largely do away with the conditions of autocracy which at present make it impossible for girls of spirit or independent character to remain in many hospitals. Inspectors should be appointed, by the Authorities to see the Act carried out. One other point we think should be dealt with by some 292/842/1/14